From friendfunding to crowdfunding: Relevance of relationships, social media, and platform activities to crowdfunding performance. (April 2018) - Borst, Irma; Moser, Christine; Ferguson, Julie
Crowdfunding involves raising small amounts of money from a large number of people, typically via the Internet and social networks, to fund a project. Crowdfunding projects are mainly funded by the project creator's relatively small network of family and friends. We argue that mobilizing funders outside this close network positively contributes to the success of a crowdfunding success. To study how project creators seek to attract funding from more distant/potential resources (latent ties) in addition to existing networks (strong and weak ties), we examined usage of social media (Facebook and Twitter) and the crowdfunding platform (website). We analyzed 10 cultural projects hosted on the Dutch crowdfunding platform "Voordekunst." Our results contribute to theorizing on latent tie activation by demonstrating that social media messages and platform updates add economic value to the crowdfunding effort. Our study also explains the moderating effect of these messages on funders of various tie strengths.